Acute admissions of patients with sickle cell disease who live in Britain. Issue 6581 (9th May 1987) - Brozović, M; Davies, S C; Brownell, A I
Abstract : All acute admissions of patients with sickle cell disease who lived in the London borough of Brent and attended this hospital were analysed for a period of one year. Sixty three of the 211 patients who were followed up by the haematology department required 161 acute admissions during the year. Most admissions (126) were for the 42 patients with homozygous sickle cell disease; 147 (91%) were for vaso-occlusive episodes, 142 of which were for painful crises, three for cerebrovascular accidents, and two for renal papillary necrosis. Preschool children with sickle cell disease were admitted predominantly with limb pain, whereas in schoolchildren and adults the incidence of trunk pain was higher. Twenty four of the 93 episodes of trunk pain culminated in an episode of severe visceral sequestration usually affecting the lungs, the liver, or the mesenteric circulation. Two patients died: an 18 month old baby with an acute splenic sequestration crisis and a 19 year old man with a severe girdle syndrome (sickling in the mesenteric circulation, liver, and lungs). Infective episodes were rare (11 episodes) but severe: one haemophilus meningitis, two salmonella infections, and three aplastic crises due to parvovirus infections. The average duration of the hospital stay was 7.4 days per admission. It is concluded that because sickle cell disease causes appreciable morbidity in older children, adolescents, and adults a systematic approach to management is needed to deal with acute episodes such as sequestration syndromes.